The Quality of Education for the People of Banyuwangi: Analysis Study of the Banyuwangi Cerdas Program - Priyanto, Hary (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
The limited ability of individuals to achieve or complete education can adversely affect poverty levels and lead to various social problems. To overcome this problem, the Banyuwangi Regency Government creates innovations in education policy through the Banyuwangi Smart program, established based on Banyuwangi Regent Regulation number 15 of 2013. This program aims to guarantee access to education up to the tertiary level to the community, with the hope of creating a quality, orderly, peaceful, and prosperous society. Although the Banyuwangi Cerdas Program is a hope for the community, not all individuals can access this program. Therefore, the purpose of this study is to describe, analyze, and interpret the Banyuwangi Smart program with the hope of expanding access to fair and equitable education for all Banyuwangi people. In this study, a qualitative approach of the case study type was used. Primary data were obtained through interviews, while secondary data were sourced from literature studies and regulations relevant to this study. The results showed that implementing the Nyuwangi Program is not always fair. This program does not cover people with low incomes in rural areas, and the assessment focuses only on aspects of cognitive intelligence without paying attention to affective and psychomotor aspects. The successful implementation of a fair Banyuwangi Smart Program requires commitment, cooperation, and harmony between the Banyuwangi Regency Government, stakeholders, education providers, and the community. Efforts should be made to expand the scope of this program to reach the communities that need it, as well as to ensure that it covers all important aspects of education, including affective and psychomotor aspects.